The lower rate of bone and joint infection in patients with open extremity fractures associated with vaccination prior to injury: a propensity-matched cohort study - Hu, Wencheng; Shi, Saiyu; Lin, Junqing; Gao, Tao; Shen, Junjie; Sun, Yi; Wei, Haifeng; Zheng, Xianyou (Frontiers in Pharmacology, 2025)
BackgroundVaccines could strengthen the innate immune system in addition to conferring protection against their target pathogen via vaccine-induced immunomodulation, a phenomenon termed trained immunity. The purpose of the present study was to determine whether vaccination prior to injury is associated with a lower rate of bone and joint infections (BJIs) in patients with open extremity fractures.MethodsPatients with open extremity fractures treated at one hospital between January 2010 and December 2019 were identified. Incidental vaccine recipients and control cohorts were matched in a 1:1 ratio using propensity scores based on age, sex, anatomical location of the fracture, Gustilo–Anderson classification, body mass index (BMI), and diagnosis of diabetes. The primary endpoint was BJIs within 1 year after initial injury. Secondary outcomes were neutrophil counts and serum C-reactive protein (CRP) levels within 24 h of admission. Logistic or linear regression was performed to control for potential confounding factors when comparing primary and secondary outcomes.ResultsVaccine inoculation history was successfully collected from 6,338 patients, with only 83 patients receiving an incidental vaccine inoculation within 3 months before injury. After propensity score matching, demographic and clinical factors were well-balanced between cohorts (all standardized differences >0.1). After controlling for potential confounders, patients in the vaccine group were at a lower risk of BJIs after open extremity fractures (vaccine, 2/83 [2.4%]; control, 10/83 [12.0%), p = 0.011). Levels of circulating neutrophils and CRP were slightly increased in the vaccine group.ConclusionVaccine inoculation is associated with the lower BJI rate after open extremity fractures, and vaccinated patients might have a more robust immune response against bacterial challenges in terms of neutrophil and CRP levels after injury. Future prospective cohort studies and clinical trials are warranted to evaluate this finding definitively.Clinical Trail registrationhttp://www.chictr.org.cn/usercenter.aspx, identifier ChiCTR2000041093.